Landuse change using Landsat TM for Cameron Highlands, Malaysia - Ramli, Mohammad Firuz; Mustapha, Saari; Yusoff, Mohd Kamil; Mohd Zin, Norsulzilah; Cheong, Sue Jen; Ying, Siew Chin; Abd Manap, Mohammad (Scientific Publishers, 2008)
A land use change study was performed at Brinchang, Cameron Highlands, Malaysia using satellite images of Lancisat TM and Landsat ETM I- acquired in 1990 and 2002. The images are classified into five land-use types: forest, urban areas, vegetable cultivation, scrubs, and tea plantations. Change detection technique was used to detect land cover changes in Brinchang, Cameron Highlands, Pahang from 1990 to 2002. The result showed that the areas of forest, tea plantation, and vegetable cultivation are increased, while urban area, and scrub are reduced. The results showed that Landsat TM may be used to monitor the land cover change.